2003
DOI: 10.1007/s00234-003-1067-0
|View full text |Cite
|
Sign up to set email alerts
|

MRI measurements of the pons and cerebellum in children born preterm; associations with the severity of periventricular leukomalacia and perinatal risk factors

Abstract: Our purpose was to measure the size of the pons and cerebellum in preterm babies with periventricular leukomalacia (PVL), and to study their relationship with the severity of PVL and with perinatal risk factors. We examined 33 premature children, mean gestational age 31 weeks, range 26-36 weeks with PVL on MRI, and 27 full-term controls. On MRI at 0.4-5.5 years (mean 1.4 years) we measured the area of the corpus callosum and vermis, the anteroposterior diameter of the pons and the volume of the cerebellum. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 31 publications
8
43
3
Order By: Relevance
“…The motor fibers descend through the basis, and the sensory fibers ascend through the tegmentum. 8,9 With regard to the size of the whole pons on MR imaging, Argyropoulou et al 10 examined 33 premature infants with PVL and reported that the AP diameter of the whole pons was significantly smaller than in a control group. However, the number of patients that they examined was relatively small, and there were no other studies regarding PVL patients evaluating the size of pons using conventional MR imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor fibers descend through the basis, and the sensory fibers ascend through the tegmentum. 8,9 With regard to the size of the whole pons on MR imaging, Argyropoulou et al 10 examined 33 premature infants with PVL and reported that the AP diameter of the whole pons was significantly smaller than in a control group. However, the number of patients that they examined was relatively small, and there were no other studies regarding PVL patients evaluating the size of pons using conventional MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the size of the whole pons on MR imaging, however, only one article has demonstrated a smaller pontine diameter in PVL children, and the number of patients that they examined was relatively small. 10 The purpose of the present study is to examine the hypothesis that the pons in patients with PVL is smaller than in normal control subjects by using a larger series.…”
mentioning
confidence: 99%
“…Studies using this protocol [21,22] have demonstrated a higher sensitivity in predicting outcomes than those applying brain US on a less frequent basis [23,24]. Serial US will not miss: (1) periventricular cysts of focal periventricular leukomalacia (PVL), which appear after the first postnatal week, progressively coalesce and then disappear at about term-equivalent age by forming the wall of the lateral ventricles [4,11]; (2) periventricular clastic lesions secondary to sepsis, necrotizing enterocolitis and viral and fungal infections developing any time in the neonatal period [11,[14][15][16]25]; (3) post-haemorrhagic ventricular dilatation that may develop any time after intraventricular hemorrhage [26], and (4) perforator stroke occurring any time after the first week and sometimes affecting the posterior limb of the internal capsule [12].…”
Section: When Do We Perform Us?mentioning
confidence: 99%
“…The incidence of posthaemorrhagic ventricular dilation is 36%, and this resolves in approximately 65% of cases [1]. Cerebellar abnormalities, mainly haemorrhage, infarction and underdevelopment, are being increasingly recognized and these have been associated with very low birth weight [4,8]. Hemispheric haemorrhage, which is the most common cerebellar haemorrhagic lesion, is usually unilateral, starting in the external granular layer [8].…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In a review of periventricular leukomalacia in preterm infants, PDA was associated with decreased cerebellar volume, area of the vermis and diameter of the pons. 6 The frequency of PDA is high in premature infants, ranging from 53% in infants born before 34-weeks gestation, up to 65% in infants born before 26-weeks gestation. 7,8 PDA in preterm infants often requires pharmacologic or surgical closure.…”
Section: Introductionmentioning
confidence: 99%